2023
DOI: 10.1038/s41467-023-39817-3
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-derived GDF-15 blocks LFA-1 dependent T cell recruitment and suppresses responses to anti-PD-1 treatment

Abstract: Immune checkpoint blockade therapy is beneficial and even curative for some cancer patients. However, the majority don’t respond to immune therapy. Across different tumor types, pre-existing T cell infiltrates predict response to checkpoint-based immunotherapy. Based on in vitro pharmacological studies, mouse models and analyses of human melanoma patients, we show that the cytokine GDF-15 impairs LFA-1/β2-integrin-mediated adhesion of T cells to activated endothelial cells, which is a pre-requisite of T cell e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 68 publications
1
14
0
Order By: Relevance
“…High expression of the integrin ITGB2 was previously shown to be associated with poor survival outcome [88], underscoring that high expression in TAMs is crucial. In contrast, ITGB2 is also associated with CD8+ T cells, as it encodes the beta chain of the LFA-1 protein, which has been shown to be essential in the assembly of the immune synapse or to influence lymphocyte extravasation and T-cell recruitment to the tumor and is regulated by GDF-15 [89]. This association is also underlined by a positive significant correlation of ITGB2 expression with M2 macrophages and, to a lesser extent, with estimated CD8+ T-cell infiltration in the TCGA cohort (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…High expression of the integrin ITGB2 was previously shown to be associated with poor survival outcome [88], underscoring that high expression in TAMs is crucial. In contrast, ITGB2 is also associated with CD8+ T cells, as it encodes the beta chain of the LFA-1 protein, which has been shown to be essential in the assembly of the immune synapse or to influence lymphocyte extravasation and T-cell recruitment to the tumor and is regulated by GDF-15 [89]. This association is also underlined by a positive significant correlation of ITGB2 expression with M2 macrophages and, to a lesser extent, with estimated CD8+ T-cell infiltration in the TCGA cohort (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In gall bladder cancer, GDF15 has been shown to increase PD-L1 expression in a PI3K/Akt/Erk dependent manner to result in immune suppression (33). In addition, a recent study has shown that GDF15 suppresses responses to anti-PD1 immune check point therapy, as GDF-15 impairs T-cell endothelial adhesion and thus recruitment to the tumor, with T-reg recruitment being less affected (34). Thus, GPX3 and GDF15 appear to share similarities in their correlation to tumor immune cell signatures.…”
Section: Discussionmentioning
confidence: 99%
“…Anamorelin, an oral ghrelin agonist, has been shown to increase oral intake and muscle mass (body weight) but not to augment the therapeutic effects of chemotherapy [28]. In addition, basic research has shown that GDF-15 is associated with metastatic potential [29], proliferative capacity [30], therapeutic e cacy [31], and decreased survival [32,33]. Moreover, anti-GDF-15 antibodies are also expected to potentiate the action of immune checkpoint inhibitors [31].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, basic research has shown that GDF-15 is associated with metastatic potential [29], proliferative capacity [30], therapeutic e cacy [31], and decreased survival [32,33]. Moreover, anti-GDF-15 antibodies are also expected to potentiate the action of immune checkpoint inhibitors [31]. Future prospective studies evaluating anorexia, weight loss, and treatment e cacy, including biomarker studies, are required to further provide further clarity.…”
Section: Discussionmentioning
confidence: 99%